2011
DOI: 10.1111/j.1574-6976.2010.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis: a matter of immune modulation

Abstract: Pertussis, or whooping cough, is a highly contagious, acute respiratory disease of humans that is caused by the Gram-negative bacterial pathogen Bordetella pertussis. In the face of extensive global vaccination, this extremely monomorphic pathogen has persisted and re-emerged, causing approximately 300,000 deaths each year. In this review, we discuss the interaction of B. pertussis with the host mucosal epithelium and immune system. Using a large number of virulence factors, B. pertussis is able to create a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
78
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 330 publications
(457 reference statements)
1
78
0
9
Order By: Relevance
“…To promote its longevity and survival within the host, B. pertussis produces a number of toxins and virulence factors (de Gouw et al, 2011). It is well established at this point that clearance of Bordetella from the host requires a Th1 response, mediated by IFN- (de Gouw et al, 2011). Experiments with vaccines have shown that augmentation of the IFN--mediated Th1 cell response leads to increased clearance of Bordetella (Marzouqi et al, 2010).…”
Section: Bordetellamentioning
confidence: 99%
See 4 more Smart Citations
“…To promote its longevity and survival within the host, B. pertussis produces a number of toxins and virulence factors (de Gouw et al, 2011). It is well established at this point that clearance of Bordetella from the host requires a Th1 response, mediated by IFN- (de Gouw et al, 2011). Experiments with vaccines have shown that augmentation of the IFN--mediated Th1 cell response leads to increased clearance of Bordetella (Marzouqi et al, 2010).…”
Section: Bordetellamentioning
confidence: 99%
“…There is even evidence that certain strains of Bordetella can invade host cells, thus avoiding many host responses (de Gouw et al, 2011). To promote its longevity and survival within the host, B. pertussis produces a number of toxins and virulence factors (de Gouw et al, 2011). It is well established at this point that clearance of Bordetella from the host requires a Th1 response, mediated by IFN- (de Gouw et al, 2011).…”
Section: Bordetellamentioning
confidence: 99%
See 3 more Smart Citations